Brain type of creatine kinase induces doxorubicin resistance via TGF-β signaling in MDA-MB-231 breast cancer cells. Issue 5 (3rd September 2022) - Son, Seogho; Yoo, Seung-ah; Nam, KeeSoo; Oh, Sunhwa; Lee, Kyung-min; Yi, Jae Youn; Shin, Incheol
ABSTRACT: Brain type of creatine kinase (CKB) regulates energy homeostasis by reversibly transferring phosphate groups between phosphocreatine and ATP at sites of high energy demand. Several types of cancer cells exhibit upregulated CKB expression, but the function of CKB in cancer cells remains unclear. In this study, we investigated the function of CKB in breast cancer by overexpressing CKB in MDA-MB-231 cells. The overexpression of CKB did not affect cell growth rate, cell cycle distribution, ATP level or key mediators of aerobic glycolysis and lactate dehydrogenase isoform levels. Meanwhile, CKB overexpression did increase resistance to doxorubicin. TGF-β-induced Smad phosphorylation and Smad-dependent transcriptional activity were significantly up-regulated by CKB expression without changes in inhibitory Smad protein levels. Moreover, treatment with TGF-β considerably enhanced cell viability during doxorubicin treatment and decreased doxorubicin-induced apoptosis in CKB-expressing MDA-MB-231 cells compared to control cells. These results suggest that CKB attenuates doxorubicin-induced apoptosis and potentiates resistance to doxorubicin by enhancing TGF-β signaling in MDA-MB-231 cells.